Zoonotic rat hepatitis E virus infection in pigs: farm prevalence and public health relevance - Javier Caballero-Gómez; Ignacio García-Bocanegra; David Cano-Terriza; María Casares-Jiménez; Saúl Jiménez-Ruiz; María A. Risalde; Lucía Ríos-Muñoz; Antonio Rivero-Juárez; Antonio Rivero (Porcine Health Management)
Abstract Rat hepatitis E virus (ratHEV) is an emerging zoonotic pathogen causing acute and chronic hepatitis, with zoonotic transmission pathways that remain unclear. While rats are its primary reservoir, recent experimental studies revealed that pigs are susceptible to ratHEV infection. To better understand its epidemiology, we assessed the herd prevalence of ratHEV in 64 extensively managed pig farms in southwestern Spain. Serum samples from 1,861 animals were pooled and analyzed using a multiplex qPCR. Viral RNA was detected in 9 (1.9%) of the 466 analyzed pools, with a herd prevalence of 10.9% (7/64; 95%CI: 5.4–20.9). Positive farms were distributed across the study area, and ratHEV circulation was limited to fattening farms (17.5%) (P = 0.007). These findings suggest pigs could act as intermediate hosts between rats and humans, posing a public health risk. Enhanced surveillance in pig farms and pork products is crucial to assess zoonotic transmission risks.